All optical controlled-NOT gate based on an exciton–polariton circuit. (July 2015) - Solnyshkov, D.D.; Bleu, O.; Malpuech, G.
Highlights: We propose an all-optical CNOT gate based on exciton–polaritons. CNOT is the basic gate required for quantum computing. We use the polariton spin to encode information. Spin-anisotropic polariton interactions are at the heart of the device. Abstract: We propose an implementation of a CNOT gate for quantum computing based on a patterned microcavity polariton system, which can be manufactured using the modern technological facilities. The qubits are encoded in the spin-coherent polariton states. The structure consists of two wire cavities oriented at 45° with a micropillar between them. The polariton spin rotates due to the Longitudinal–Transverse splitting between polarization eigenstates in the wires. In the pillar, the optically generated circularly polarized polariton macrooccupied state plays the role of the control qubit. Because of the spin-anisotropic polariton interaction, it induces an effective magnetic field along the Z -direction with a sign depending on the qubit value.